The new lesbian aesthetic? Exploring gender style among femme, butch and androgynous sexual minority women - Gunn, Audrey; Hoskin, Rhea Ashley; Blair, Karen L. (Women's Studies International Forum, 2021)
The current study explored sexual minority women’s gender aesthetic and style by using van Anders’ (2015) sexual configurations theory (SCT), which allows for nuance in the measurement of gender/sex research. Previous research on sexual minority women has suggested a markedly masculine “Lesbian Aesthetic” (Huxley et al., 2014) and has connected aesthetic expression to internalized homophobia and levels of outness such that sexual minority women categorized as more feminine report higher rates of internalized homophobia and identity concealment. However, the bulk of past research used dichotomous measures of assessing gender and predated an ostensible shift in LGBTQ+ identities. To update this body of research, the current study explored gender aesthetics by asking sexual minority women to map their gender expression using SCT diagrams and complete measures of outness and internalized homophobia. We found no significant group differences in internalized homophobia or outness for femme, butch, and androgynous participants. Content analyses of gender diagrams suggest that the gender aesthetics of sexual minority women are neither monolithic nor masculine but may be beginning to lean towards the feminine and most certainly encompass a complex and diverse range of expressions
Keywords: amériques; approches et analyses; canada; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; psychologie; queer; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Beyond the superordinate categories of “Gay Men” and “Lesbian Women”: Identification of gay and lesbian subgroups - McCutcheon, Jessica M.; Morrison, Melanie A. (Journal of Homosexuality, 2021)
Nation-wide opinion polls and social scientific studies indicate that evaluations of gay men and lesbian women have become increasingly favourable. These positive trends do not explain the widespread discrimination experiences being reported. To assist researchers in investigating attitudes towards gay and lesbian persons, the current research examines whether there are multiple “types” that are identifiable and salient. Two Canadian studies (Ns = 67 and 206) were conducted to establish the presence of gay and lesbian subgroups. Using subgroups generated by Study 1 participants, community and student sub-samples selected those they perceive to exist. Results indicated that, for gay men, the subgroups Drag Queen and Flamboyant emerged, as did Butch for lesbian women. Amongst students, Closeted and Feminine also emerged for gay men, as well as Feminist and Tomboy for lesbian women. These findings have implications for contemporary research on gay- and lesbian-related attitudes and the methodology used to assess them.
Keywords: amériques; canada; discipline; identités LGBTQIA2+; psychologie; ressource en ligne; régions géographiques; sciences humaines

Mothers and mental labor: A phenomenological focus group study of family-related thinking work - Robertson, Lindsey G.; Anderson, Tamara L.; Hall, M. Elizabeth Lewis; Kim, Christina Lee (Psychology of Women Quarterly, 2019)
Le travail mental est une composante peu étudiée et longtemps invisible du travail familial. Les chercheurs ont décrit le travail mental comme important, éprouvant et effectué de manière disproportionnée par les mères par rapport aux pères. Cependant, les définitions opérationnelles utilisées dans ces études n'étaient que préliminaires et manquaient de terminologie unifiée. En réponse aux appels à une vision élargie du travail domestique et à de meilleures définitions de son contenu, nous avons entrepris une enquête phénoménologique sur le travail mental familial effectué par les mères. Notre analyse phénoménologique interprétative de sept entretiens de groupe a produit une définition du travail mental des mères et de ses composantes qui était empiriquement fondée sur l'expérience vécue des mères de jeunes enfants ( N = 25). Distinct des tâches ménagères, de la garde des enfants et du travail émotionnel, le travail mental est apparu comme une activité de réflexion effectuée dans le but d'atteindre des objectifs familiaux. Nous avons identifié six formes de travail mental : (a) la planification et l'élaboration de stratégies, (b) le suivi et l'anticipation des besoins, (c) la métaparentalité, (d) la connaissance (apprentissage et mémorisation), (e) la pensée managériale (y compris la délégation et l'instruction) et (f) l'autorégulation. Toutes les mères participantes se sont présentées comme le principal travailleur mental de leur famille, quel que soit leur statut d'emploi ou le niveau d'implication de leur partenaire. Notre description du travail mental peut aider les parents, les chercheurs, les cliniciens, les décideurs politiques et les éducateurs à reconnaître, à valoriser et à mieux tenir compte de la dynamique du travail mental à l'œuvre dans la construction de la vie familiale, la reproduction des rôles de genre et la perpétuation des écarts entre les sexes dans la division du travail familial et la charge mentale.
Keywords: 2000 à aujourd'hui; amériques; charge mentale; discipline; famille; famille hétérosexuelle; maternité; projet charge mentale; psychologie; périodes historiques; régions géographiques; sciences humaines; thématiques; travail; travail familial; travail invisible; états-unis

Dancing backwards in high heels: Female professors experience more work demands and special favor requests, particularly from academically entitled students - El-Alayli, Amani; Hansen-Brown, Ashley A.; Ceynar, Michelle (Sex Roles, 2018)
Although the number of U.S. female professors has risen steadily in recent years, female professors are still subject to different student expectations and treatment. Students continue to perceive and expect female professors to be more nurturing than male professors are. We examined whether students may consequently request more special favors from female professors. In a survey of professors (n = 88) across the United States, Study 1 found that female (versus male) professors reported getting more requests for standard work demands, special favors, and friendship behaviors, with the latter two mediating the professor gender effect on professors’ self-reported emotional labor. Study 2 utilized an experimental design using a fictitious female or male professor, with college student participants (n = 121) responding to a scenario in which a special favor request might be made of the professor. The results indicated that academically entitled students (i.e., those who feel deserving of success in college regardless of effort/performance) had stronger expectations that a female (versus male) professor would grant their special favor requests. Those expectations consequently increased students’ likelihood of making the requests and of exhibiting negative emotional and behavioral reactions to having those requests denied. This work highlights the extra burdens felt by female professors. We discuss possible moderators of these effects as well as the importance of developing strategies for preventing them. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: amériques; approches et analyses; discipline; femmes professeures; milieux universitaires; projet charge mentale; psychologie; psychologie sociale; rapports sociaux de sexe; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; travail émotionnel; états-unis

Régulation des émotions et troubles de comportement chez des enfants d'âge préscolaire victimes d'agression sexuelle - Langevin, Rachel (Université du Québec à Montréal, 2015)
Être victime d'agression sexuelle (AS) durant l'enfance est associé à d'importants problèmes de santé mentale, physique et sexuelle à l'âge scolaire comme à l'âge adulte (Maniglia, 2009; Yancey, Hansen, & Naufel, 2011). Bien qu'une proportion non négligeable des AS de mineurs implique des enfants d'âge préscolaire, nous disposons de peu d'informations sur les corrélats des AS chez ces enfants. Les quelques études disponibles montrent, néanmoins, que leurs difficultés semblent similaires à celles des enfants d'âge scolaire (Berthelot, Langevin, & Hébert, 2012). On sait, par ailleurs, que les enfants victimes de diverses formes de maltraitance (négligence, agression physique et sexuelle) présentent davantage de difficultés de régulation des émotions que les enfants non maltraités. La régulation des émotions serait une variable médiatrice des liens entre maltraitance et troubles de comportement intériorisés et extériorisés (Alink, Cicchetti, Kim, & Rogosch, 2009). Cette thèse a pour objectif d'examiner les liens entre l'AS, la régulation des émotions et les troubles de comportement intériorisés et extériorisés chez des enfants d'âge préscolaire. Ses objectifs spécifiques, qui font chacun l'objet d'un article, sont les suivants : a) comparer les compétences de régulation des émotions d'enfants d'âge préscolaire victimes d'AS à celles d'enfants du même âge, mais n'ayant pas vécu un tel trauma, et b) examiner les liens entre AS, régulation des émotions et troubles de comportements intériorisés et extériorisés à l'aide d'une analyse de médiation. La thèse comprend quatre chapitres. Le premier chapitre offre une recension des écrits scientifiques portant sur les AS (définition, prévalence, corrélats), la régulation des émotions (définition et développement) et sur les liens empiriques et conceptuels entre régulation des émotions, santé mentale et maltraitance. Le premier article constitue le second chapitre. Les parents et les éducateurs ont évalué les compétences de régulation des émotions d'enfants d'âge préscolaire victimes d'AS (n = 62) et d'enfants du même âge n'ayant pas subi d'AS (n = 65) à l'aide du Emotion Regulation Checklist (ERC; Shields & Cicchetti, 1997). Les enfants ont, pour leur part, complété la MacArthur Story Stem Battery (Bretherton & Oppenheim, 2003) qui a ensuite été codifiée selon une grille, adaptée pour la présente étude, permettant d'obtenir des indices de leurs compétences de régulation des émotions (Langevin, Cassette, & Hébert, 2014). Les résultats indiquent que les enfants agressés sexuellement présentent de moins bonnes compétences de régulation des émotions que les enfants du groupe de comparaison sur plusieurs indicateurs provenant des trois évaluations. Les garçons victimes d'AS obtiennent des scores de régulation des émotions particulièrement faibles. Le deuxième article forme le troisième chapitre. Une analyse de médiation-modérée a servi à examiner les liens entre l'AS, la régulation des émotions, telle qu'évaluée par les parents et les éducateurs à l'aide du ERC, et les troubles de comportement intériorisés et extériorisés évalués par les parents à l'aide du Child Behavior Checklist (Achenbach & Rescorla, 2000; 2001). Les résultats montrent que l'association entre l'AS et les troubles intériorisés est entièrement médiatisée par la régulation des émotions, mais que la médiation est partielle pour ce qui est des troubles extériorisés. Le genre des enfants apparait comme une variable modératrice du lien entre l'AS et la régulation des émotions lorsque l'évaluation des parents est utilisée, alors qu'il modère l'association entre l'AS et les troubles de comportement lorsque l'évaluation des éducateurs est utilisée. Le quatrième et dernier chapitre de la thèse intègre les résultats obtenus dans les deux études et en souligne les contributions et limites. Enfin, ce chapitre aborde les pistes de recherche futures et les implications cliniques des résultats de la thèse. ______________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : agression sexuelle, régulation des émotions, troubles de comportement intériorisés, troubles de comportement extériorisés, préscolaire
Keywords: IREF; amériques; discipline; enfants; mémoires/thèses; psychologie; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; violences; violences sexuelles

Young, Black and male : Exploring the intersections of racial and gender identity in an all-Black male high school - Rogers, Leoandra Onnie (New York University, 2012)
From popular culture to academia, there is national panic about the dismal life trajectories of Black males. This "Black male crisis" has contributed to emergent all-Black, all-male schools. Racial identity is commonly used to explain underperformance among Blacks, yet within-group gender disparity signifies the importance of gender relative to race. Minimal research exists on Black males' gender identities, and less on the intersections of gender and race. This longitudinal dissertation used quantitative and qualitative data to examine the development and intersections of racial and gender identity among Black adolescent males transitioning from co-educational grammar schools and entering the ninth grade at an all-Black, all-male high school. Findings are presented in two empirical papers. Paper 1 examined survey data collected from Black males (N = 183) to explain how boys' racial and gender identities were interrelated, changed over time, and influenced their psychological and academic adjustment. Results from the growth curve analysis revealed that boys' racial and gender identities were interrelated with each other and that higher levels of identity attachment were associated with better psychological and academic adjustment. Moreover, the strength of the relationship between gender identity and psychological adjustment increased over time, indicating that gender identity became increasingly important for boys' wellbeing. Paper 2 analyzed interview data with a subsample of Black males (n = 21) to examine how they resisted and accommodated racial and gender stereotypes. Results from the qualitative analysis revealed that boys were aware of the ways that racial and gender stereotypes overlap, but they responded to these stereotypes in different ways. Although some boys accommodated to both racial and gender stereotypes and others resisted these stereotypes, the majority of the boys responded by accommodating to gender stereotypes and resisting racial stereotypes. That is, they tended to perpetuate cultural stereotypes that require males to be the leader, emotionally stoic, and not to be feminine (i.e., gay) while challenging beliefs about the intellectual inferiority and incompetence of Black people. Findings are interpreted within the macro-context of cultural stereotypes and the micro-context of an all-Black male school. Implications for the study of identity, Black males, and single-sex education are discussed.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; adolescence; amériques; approches et analyses; chicago; discipline; genre; hommes* noirs; identité raciale; intersectionnalité; mémoires/thèses; philosophie; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes; étude longitudinale; étude qualitative; étude quantitative

Cerveau, sexe et préjugés - Vidal, Catherine (Cerveau, hormones et sexe: Des différences en question, 2012)
"Les différences psychologiques entre les sexes suscitent un intérêt considérable, tant dans les milieux de la recherche que dans les médias. On ne compte plus le nombre de publications scientifiques, d'ouvrages de vulgarisation ou de reportages consacrés à ces questions. Pourtant, une large part de l'information diffusée tient davantage du préjugé, du parti pris idéologique, que d'une démarche scientifique rigoureuse. Les femmes seraient ainsi plus douces, mieux disposées à prendre soin des autres, incapables de lire une carte routière, alors que les hommes seraient bons en maths, compétitifs, plus agressifs. Comment expliquer la persistance de tels mythes aujourd'hui encore ? C'est de ce constat, et d'un certain sentiment d'exaspération, qu'est né le présent ouvrage. Il réunit des chercheures de différentes disciplines : neurobiologie, psychologie, sociologie, science politique. S'appuyant, notamment, sur les données les plus récentes en neurosciences et en psychologie comparée des sexes, ces dernières proposent une synthèse des connaissances actuelles et une réflexion sur la différenciation psychologique des sexes, sur l'orientation sexuelle et sur les notions de sexe et de genre inspirée des textes d'auteures féministes. Il ne s'agit plus de savoir si le cerveau a un sexe, mais si cette question est pertinente et, surtout, pour qui ?"--Page 4 de la couverture.
Keywords: amériques; analyse différenciée selon les sexes -ADS+; approches et analyses; biologie; corps; cours; discipline; discours dominant; fem1000; hétéronormativité; hétérosexisme; neurobiologie; neuropsychologie; pol4102; premier cycle; psy4910; psychologie; québec; régions géographiques; santé; science politique; science politique et droit; sciences; sciences humaines; sexe/genre; sexisme; sociologie; stéréotypes; stéréotypes de genre; systèmes d'oppressions; thématiques; études de genres

Ethnic, Gender, and Acculturation Influences on Sexual Behaviors - Meston, Cindy M.; Ahrold, Tierney (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
Much research has been conducted on ethnic differences in sexuality, but few studies have systematically assessed the importance of acculturation in sexual behavior. The present study assessed general differences in normative sexual practices in healthy Euro-American, Asian, and Hispanic populations, using measures of acculturation to analyze the relative effects of heritage and mainstream cultures within each group. A total of 1,419 undergraduates (67% Euro-American, 17% Hispanic, 16% Asian; 33% men, 67% women) completed questionnaires which assessed sexual experience and causal sexual behaviors. In concordance with previous studies, Asians reported more conservative levels of sexual experience and frequency of sexual behaviors, fewer lifetime partners, and later ages of sexual debut than Euro-American or Hispanic counterparts. Hispanic reported sexual experiences similar to that of Euro-Americans. There was a significant interaction between mainstream and heritage acculturation in predicting number of lifetime sexual partners in Asian women such that the relationship between heritage acculturation and casual sexual behavior was stronger at lower levels of mainstream acculturation. On the other hand, in Hispanic men, higher levels of mainstream acculturation predicted more casual sexual behavior (one-time sexual encounters and number of lifetime sexual partners) when heritage acculturation was low but less casual sexual behavior when heritage acculturation was high. These results suggest that, for sexual behavior, Hispanic men follow an “ethnogenesis” model of acculturation while Asian women follow an “assimilation” model of acculturation.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexualité; thématiques; états-unis

The Role of Gender and Ethnicity in Perceptions of Rape and Its Aftereffects - Schneider, Lawrence J.; Mori, Lisa T.; Lambert, Paul L.; Wong, Anna O. (Sex Roles : A Journal of Research, 2009)
Caucasian-, Hispanic-, and Asian-American male and female students (n = 764) attending a California (USA) public university reported their perceptions of sexual assault. After reading a rape vignette, participants gave their impressions of the victim; estimated time needed for recovery and treatment; and recommended a sentence for the assailant. Half of the sample received information regarding state sentencing guidelines. Relative to female participants, males perceived the victim as more responsible. Caucasian-American males had stronger reservation about the victim’s judgment. Males were less inclined to assign blame than were females. Ethnicity was the only factor influencing perceptions of recovery. Ethnicity and sentencing guidelines, but not gender, impacted imprisonment decisions. Issues impeding a unified theoretical understanding of perceptions of rape victims were considered.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; californie; cours; discipline; intersectionnalité; perception; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; thématiques; viol; violences; états-unis

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Collection Santé et société, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Une voix différente : pour une éthique du care - Gilligan, Carol (Flammarion, 2008)
La morale a-t-elle un sexe ? Les femmes et les hommes ont-ils un sens différent de la moralité ? Une telle question donne la mesure de l'immense débat qu'a suscité le livre de Carol Gilligan, catalyseur des réflexions féministes sur l'éthique du care (imparfaitement traduit par " sollicitude "). Si les analyses en termes de genre sont désormais connues, l'idée de care n'a pas rencontré un aussi large accueil. L'intérêt public grandissant pour les questions d'aide aux personnes vulnérables, et pour les problèmes sociaux et politiques engendrés par la situation inégalitaire des travailleuses/eurs du care et leur circulation au niveau mondial, a permis que les questions théoriques liées au care trouvent une nouvelle pertinence. Il a fallu également que se dissipe le rapport ombrageux du féminisme aux questions morales pour que le care ne soit pas rabattu sur l'idée d'un " service " contraint au profit des plus puissants. Aux Etats-Unis, Une voix différente est le texte le plus lu et le plus cité de la " seconde vague " du féminisme. Il a ouvert un débat politique crucial, entre éthique de la justice et éthique du care, entre une moralité centrée sur l'équité, l'impartialité et l'autonomie et une moralité formulée " d'une voix différente ", reconnue le plus souvent dans l'expérience des femmes, et fondée non sur des principes mais sur une question : comment faire, dans une situation donnée, pour préserver et entretenir les relations humaines qui y sont en jeu ?
Keywords: 1900-1999; amériques; care; cours; discipline; fem1000; har4600; phi4336; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis; éthique

The Politics of Protection: Body Image, Social Pressures, and the Misrepresentation of Young Black Women - Poran, Maya A. (Sex Roles : A Journal of Research, 2006)
As part of a larger multi-method study, 15 Black women college students participated in focus group discussions on the body. Contrary to popular theories that propose that Black women are protected by a “Black Culture” that buffers them from negative effects of body representations—thereby leaving them with higher body esteem—the themes that emerged in the focus group discussions indicate that young Black women are indeed feeling (1) pressures to be thin, (2) pressures from the preferences of men of diverse ethnicities, (3) competition with other Black women in the realms of beauty, and (4) a strong sense of being misrepresented by media images of thin Black women. These results not only indicate that body image issues are of real pressing concern to young Black women, but that psychological research methodologies may be adding to the misrepresentation of young Black women and their struggles. Qualitative methods must be utilized in order to hear more clearly the voices of Women of Color.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; corps; cours; discipline; féminisme afroaméricain; image corporelle; intersectionnalité; new york; premier cycle; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; thématiques; états-unis

Grossesse hors mariage dans les familles haïtiennes - Raphaël, Frantz (Santé mentale au Québec, 2006)
Des grossesses précoces chez des jeunes adolescentes haïtiennes de Montréal entraînent des situations de crise qui touchent plusieurs familles, en plus d’interpeller et d’impliquer des intervenants de diverses disciplines. Le sujet, abordé dans un contexte transculturel, fait référence au biculturalisme haïtien, tant en Haïti qu’en terre étrangère. Dans cet article, l’auteur aborde plus particulièrement la situation des Haïtiens dans le contexte québécois. L’analyse de l’attitude des parents des deux groupes culturels, occidentalisé et créole, constitue une lumière médiatrice dans les relations d’aide ou d’intervention psychothérapeutique. Dans la communauté haïtienne, les problèmes d’identité culturelle d’une part, et, le manque d’affiliation à la famille, d’autre part, sont à la base des conflits entre parents et enfants. L’auteur conclut avec des propositions dans le but d’améliorer l’efficacité des interventions avec ces familles dans leur processus d’adaptation migratoire.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; conflit familial; cours; discipline; grossesse hors mariage; haïti; justice sociale; maternité; montréal; premier cycle; psychologie; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; sex2283; sexualité; thématiques

The impact of culture and minority status on women's experience of domestic violence - Kasturirangan, Aarati; Krishnan, Sandhya; Riger, Stephanie (Trauma, violence & abuse, 2004)
The influence of culture and ethnic background on women’s experience of domestic violence has been explored in research only recently. Here the authors review research about the impact of culture and minority status in the United States on women’s experience of domestic violence, considering family structure,immigration, acculturation, oppression, and community response. The authors encourage researchers and service providers to acknowledge the effects on women of sociopolitical dynamics, including racism, and to identify specific aspects of culture that are relevant to intimate partner abuse.
Keywords: amériques; approches et analyses; cours; discipline; intersectionnalité; justice sociale; pauvreté; premier cycle; psychologie; racisme; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

Do Racial Minorities Respond in the Same Way to Mainstream Beauty Standards? Social Comparison Processes in Asian, Black, and White Women - CHIN EVANS, PEGGY; McCONNELL, ALLEN R. (Self and Identity, 2003)
Some members of stigmatized groups, such as Asian women, may be more likely to experience negative self-evaluations after exposure to a mainstream beauty standard than members of other stigmatized groups, such as Black women. In this study, 54 Asian women, 52 Black women, and 64 White women, were exposed to mainstream standards of beauty and compared themselves to these idealized images. It was hypothesized that although Black women would find these comparisons irrelevant, Asian women would see these targets as relevant for their comparisons, reflecting their striving for mainstream beauty standards. The results indicated that Black women did not find mainstream standards as relevant to themselves, and reported positive self-evaluations generally and about their bodies in particular. Asian women, on the other hand, responded differently than Black women and were more likely to endorse mainstream beauty standards in a similar fashion to White women. As predicted, Asian women also experienced greater dissatisfaction with their bodies than did Black women.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; corps; cours; discipline; intersectionnalité; premier cycle; psychologie; périodes historiques; racisme; représentation; ressource en ligne; régions géographiques; santé; santé mentale; sciences humaines; sex2283; sexisme; systèmes d'oppressions; thématiques; états-unis

Butch/Femme in the personal advertisements of lesbians - Smith, Christine A.; Stillman, Shannon (Journal of Lesbian Studies, 2002)
Personal advertisements placed by lesbians were examined to determine how often butch/femme descriptors were used: (a) as a form of self-identification or (b) to indicate the type of partner being sought. The 388 personal advertisements were drawn from 16 alternative newspapers around the U.S., as well as from one Internet site (Qworld) that contained personal ads by lesbians. Each advertisement was coded for the presence or absence of butch/femme descriptors. The majority of advertisers did not mention butch or femme labels either in terms of self-identity or type of partner sought. Among the minority of advertisers who self-identified as butch or femme, more described themselves as femme than butch. Among advertisers seeking butch or femme partners, femme partners were sought most often. Explanations for the preference for femme lesbians were explored
Keywords: amériques; butch/femme; discipline; identités LGBTQIA2+; psychologie; ressource en ligne; régions géographiques; sciences humaines; états-unis

Woman: An intimate geography - Angier, Natalie (Anchor Books, 2000)
Woman is a fascinating, fact-filled guide that covers everything from organs to orgasms, hormones to hysterectomies. With her characteristic clarity, insight, and sheer exuberance of language, bestselling author Natalie Angier cuts through the still-prevalent myths and misinformation surrounding the female body, that most enigmatic of evolutionary masterpieces. With a witty and assured narrative, and a reader-friendly dose of science, Woman is an essential and engaging resource for all time.
Keywords: amériques; approches et analyses; biologie; corps; cours; différence des sexes; discipline; fem1000; médecine; premier cycle; psychologie; rapports sociaux de sexe; régions géographiques; santé; sciences; sciences humaines; stéréotypes; thématiques; états-unis

Une si grande différence - Gilligan, Carol (Flammarion, 1986)
Cela fait des siècles que nous écoutons les voix des hommes et les théories que leur dicte leur expérience. Plus récemment, nous avons commencé, non seulement à remarquer le silence des femmes, mais aussi, la difficulté d'entendre ce qu'elles disent quand elles prennent la parole. " A partir de trois enquêtes psychologiques, Carol Gilligan montre bien que la grande différence entre le masculin et le féminin est une différence de formation et de comportement moral conduisant à deux types psychologiques bien distincts, les femmes se caractérisant par une éthique de sollicitude qui influence leur rapport avec autrui et leur sens des responsabilités. Best-seller aux U.S.A., Une si grande différence est un ouvrage capital du post-féminisme.
Keywords: 1900-1999; amériques; care; cours; différence des sexes; discipline; fem1000; postféminisme; premier cycle; psychologie; périodes historiques; régions géographiques; sciences humaines; thématiques; états-unis; éthique

L'Envers de la nuit: les femmes contre la pornographie - Lederer, Laura; Audy, Monique; Dufresne, Martin (Collection Les Entêtées, 1983)
Keywords: 1900-1999; amériques; approches et analyses; corps; cours; discipline; droit; féminisme pop; premier cycle; psychologie; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis